Implementing Project Based Learning in Mathematics Learning Media Course - Hajerina, Hajerina; Suciati, Indah; Ayulinansyah, Sri; Wahyuni, Dewi Sri (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
In order to describe the implementation of PjBL in the Mathematics Learning Media course as a learning assessment material, a classroom action research (PTK) was conducted. The research subjects were 3rd semester students of Mathematics Education at Alkhairaat University Palu in the academic year 2023/2024. Data were collected through observation, interviews, questionnaires, and documentation, which were then analysed using the Miles & Huberman model. In addition, data triangulation was also carried out to obtain valid and credible data. The results of this study resulted in 7 (seven) evaluation materials, namely the effectiveness of PjBL, challenges of PjBL implementation, students' reactions, students' skills, students' creativity, use of learning media and recommendations for improvement. With these findings, it is hoped that it can be our concern so that we can correct deficiencies and improve the learning process.